Reciprocal expression of the endocytic protein HIP1R and its repressor FOXP1 predicts outcome in R-CHOP-treated diffuse large B-cell lymphoma patients. - Wong, K; Gascoyne, D; Brown, P; Soilleux, E; Snell, C; Chen, H; Lyne, L; Lawrie, C; Gascoyne, R; Pedersen, L; Møller, M; Pulford, K; et al. (2014)
We previously identified autoantibodies to the endocytic-associated protein Huntingtin-interacting protein 1-related (HIP1R) in diffuse large B-cell lymphoma (DLBCL) patients. HIP1R regulates internalization of cell surface receptors via endocytosis, a process relevant to many therapeutic strategies including CD20 targeting with rituximab. In this study, we characterized HIP1R expression patterns, investigated a mechanism of transcriptional regulation and its clinical relevance in DLBCL patients treated with immunochemotherapy (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone, R-CHOP). HIP1R was preferentially expressed in germinal center B-cell-like DLBCL (P<0.0001) and inversely correlated with the activated B-cell-like DLBCL (ABC-DLBCL) associated transcription factor, Forkhead box P1 (FOXP1). HIP1R was confirmed as a direct FOXP1 target gene in ABC-DLBCL by FOXP1-targeted silencing and chromatin immunoprecipitation. Lower HIP1R protein expression (≤ 10% tumoral positivity) significantly correlated with inferior overall survival (OS, P=0.0003) and progression-free survival (PFS, P=0.0148) in R-CHOP-treated DLBCL patients (n=157). Reciprocal expression with ≥ 70% FOXP1 positivity defined FOXP1(hi)/HIP1R(lo) patients with particularly poor outcome (OS, P=0.0001; PFS, P=0.0016). In an independent R-CHOP-treated DLBCL (n=233) microarray data set, patients with transcript expression in lower quartile HIP1R and FOXP1(hi)/HIP1R(lo) subgroups exhibited worse OS, P=0.0044 and P=0.0004, respectively. HIP1R repression by FOXP1 is strongly associated with poor outcome, thus further understanding of FOXP1-HIP1R and/or endocytic signaling pathways might give rise to novel therapeutic options for DLBCL.